Phase separation in iron chalcogenide superconductor Rb0.8+xFe1.6+ySe2 as seen by Raman light scattering and band structure calculations - Pashkevich, Yu.; Pomjakushina, E.; Gnatchenko, S.; Wulferding, D.; Lamonova, K.; Gusev, A.; Shevtsova, T.; Lemmens, P.; Gnezdilov, V.; Conder, K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
We report Raman light scattering in the phase separated superconducting single crystal Rb0.77Fe1.61Se2 with Tc = 32 K over a wide temperature region 3–500 K. The observed phonon lines from the majority vacancy ordered Rb2Fe4Se5 (245) antiferromagnetic phase with TN = 525 K demonstrate modest anomalies in the frequency, intensity and halfwidth at the superconductive phase transition. We identify phonon lines from the minority compressed RbδFe2Se2 (122) conductive phase. The superconducting gap with dx2-y2 symmetry has been detected in our spectra. In the range 0–600 cm–1 we observe a weak but highly polarized B1g-type backgroundwhich becomes well-structured upon cooling. A possible magnetic or multiorbital origin of this background is discussed. We argue that the phase separation in M0.8+xFe1.6+ySe2 is of pure magnetic origin. It occurs below the Néel temperature when the magnetic moment of iron reaches a critical value. We state that there is a spacer between the majority 245 and minority 122 phases. Using ab initio spin-polarized band structure calculations we demonstrate that the compressed vacancy ordered Rb2Fe4Se5 phase can be conductive and therefore may serve as a protective interface spacer between the purely metallic RbδFe2Se2 phase and the insulating Rb2Fe4Se5 phase providing percolative Josephson-junction like superconductivity all throughout of Rb0.8+xFe1.6+ySe2. Our lattice dynamics calculations show significant differences in the phonon spectra of the conductive and insulating Rb2Fe4Se5 phases.